Sele????o de projetos no setor p??blico: uma an??lise no poder judici??rio estadual brasileiro - Teixeira, Rodrigo (2018)
Project selection is a useful activity for companies that need to choose one or more set of projects. Archer and Ghasemzadeh (1999) define project selection as a periodic activity to choose a set of projects. The project selection process is present in both private and public institutions and aims to maximize the results for the organization. In the public sector, implementations of project selection techniques arise with the implementation of the model called New Public Management, which applies techniques of the private sector to raise the results. According to Litvinchev et al. (2010) research in the process of project selection in the public sector still lacks attention on the part of the researchers when compared to research in the private sector. Seeking to fill the gap in project selection studies in the public sector, this research project analyzed how the practice of project selection influences the performance of the project portfolio of the State Judicial Branch. To achieve this objective, a qualitative exploratory research was carried out using a multiple case study strategy. Three cases representing different regions of the country were selected. It was concluded that the project selection activity in the state Judiciary is occurring in a disorganized way, using only some phases of the project selection process presented in the literature. The absence of a standardized model has generated a portfolio with excess of projects, unbalanced and with low alignment. Therefore, the performance of the institution is being affected, with high congestion rates and low rate of attendance to the demands.